Azithromycin promotes proliferation, and inhibits inflammation in nasal epithelial cells in primary ciliary dyskinesia - Varenyiova, Zofia; Rojas-Hernandez, Laura S; Spano, Jacquelyn; Capek, Vaclav; Rosenberg-Hasson, Yael; Holmes, Tyson; Milla, Carlos (Scientific reports, 2023)
Primary ciliary dyskinesia (PCD) is a genetic disorder associated with recurrent and chronic respiratory infections due to functional defects of motile cilia. In this study, we aimed to elucidate inflammatory and proliferative responses in PCD respiratory epithelium and evaluate the effect of Azithromycin (AZT) on these responses. Airway basal cells (BCs) were isolated from nasal samples of Wild-type (WT) epitope of healthy donors and PCD donors with bi-allelic mutations in DNAH5, DNAH11 and CCDC39. Cells were expanded in vitro and stimulated with either Lipopolysaccharide (LPS) or vehicle control. Post stimulation, cells were treated with either Azithromycin (AZT) or vehicle control. Cell proliferation was imaged in real-time. Separately, BCs from the same donors were expanded and grown at an air-liquid interface (ALI) to generate a multi-ciliated epithelium (MCE). Once fully mature, cells were stimulated with LPS, AZT, LPS + AZT or vehicle control. Inflammatory profiling was performed on collected media by cytokine Luminex assay. At baseline, there was a significantly higher mean production of pro-inflammatory cytokines by CCDC39 BCs and MCEs when compared to WT, DNAH11 and DNAH5 cells. AZT inhibited production of cytokines induced by LPS in PCD cells. Differences in cell proliferation were noted in PCD and this was also corrected with AZT treatment.
Keywords: cytokiny; Lipopolysaccharides; zánět; proliferace buněk; epitelové buňky; Epithelial Cells; Ciliary Motility Disorders; azithromycin; Humans; Azithromycin; Inflammation; Cell Proliferation; Cytokines; lipopolysacharidy; poruchy ciliární motility; lidé